The Briar Club : a novel - Quinn, Kate (New York, NY : William Morrow, an imprint of HarperCollins Publishers, 2024)
"Washington, D.C., 1950. Everyone keeps to themselves at Briarwood House, a down-at-the-heels all-female boardinghouse in the heart of the nation's capital, where secrets hide behind white picket fences. But when the lovely, mysterious widow Grace March moves into the attic, she draws her oddball collection of neighbors into unlikely friendship: poised English beauty Fliss whose facade of perfect wife and mother covers gaping inner wounds; police officer's daughter Nora, who is entangled with a shadowy gangster; frustrated baseball star Bea, whose career has ended along with the women's baseball league of WWII; and poisonous, gung-ho Arlene, who has thrown herself into McCarthy's Red Scare. Grace's weekly attic-room dinner parties and window-brewed sun tea become a healing balm on all their lives, but she hides a terrible secret of her own. When a shocking act of violence tears apart the house, the Briar Club women must decide once and for all: Who is the true enemy in their midst?"--Dust jacket flap.
"The New York Times bestselling author of The Diamond Eye and The Rose Code returns with a haunting and powerful story of female friendships and secrets in a Washington, DC, boardinghouse during the McCarthy era"--
Includes recipes.
Keywords: Female friendship -- Fiction; Women -- Fiction; Secrecy -- Fiction; Boardinghouses -- Washington (D.C.) -- Fiction; Anti-communist movements -- Fiction; Nineteen fifties -- Fiction; Attics -- Fiction; Washington (D.C.) -- Fiction; Political fiction; Historical fiction; Novels